Production and Promotion of Triticale as a High Quality Fodder and Feed in Small-Scale Dairy Farmers of Bangladesh - Haque, ME; Waddington, SR; Sarker, ZI; Sarker, NR; Akteruzzaman, M (Progressive Agriculture, 2013)
In Bangladesh, high quality fodder is scare from December to May for ruminant livestock and feed is expensive throughout the year for poultry. A project was conducted in the cool dry Rabi (December-February) seasons of 2005-06 and 2006-07 to promote triticale (X Triticosecale Wittmack) as a high quality dual-purpose fodder and feed for small-scale dairy and poultry producers. During 2005 and 2006, 504 farm families from six districts in north western and central Bangladesh received training on triticale cultivation and its utilization as a green fodder for dairy cows and for grain. Printed training manuals and visual training materials (including a DVD docudrama) were developed, used in training, and distributed widely. On-farm demonstrations on triticale production were mounted with each trained farm family in two years using a dual-purpose fodder and grain type triticale variety, WRF-7, that earlier on farm research had identified to perform well in Bangladesh. High quality grass fodder was obtained by cutting the vegetative triticale plants either twice (at 35 and 50 days after seeding (DAS)or once (at around 40 days), while the later ratooning tillers produced grain. In 168 farmer demonstrations in 2005-06, the green fodder yield ranged from 4.9 to 20.0 t/ha fresh mass (0.7 t/ha to 2.7 t/ha dry mass) from one cut at 35 DAS and 7 to 28 t/ha fresh mass from two cuts at 35 and 50 DAS. Overall, 62% of farmers reported yields above 10 t/ha of fresh green fodder. A mean grain yield of 1.8 t/ha was obtained from WRF-7 after two cuts on-farm. Straw yields ranged from 0.8 to 7.1 t/ha dry mass. 324 farmers hosted similar demonstrations in 2006-07 and reported higher yields of green fodder, ranging from 7.4 to 33.7 t/ha fresh mass from one cut at 40 to 42 DAS. A higher mean grain yield of 2.8 t/ha was obtained from WRF-7 after one cut for fodder in 2006-07. Assessments of WRF-7 dual-purpose triticale by farmers were very positive, with 97% wanting to grow triticale again in more land ranging from 0.04 ha to 0.81 ha (Table 3). From experience, many farmers decided it was more efficient to cut triticale once for green fodder. Almost all farmers reported benefits to milk production and farm income from feeding triticale fodder to cows. It was concluded that smallholder dairy farmers in North-West Bangladesh can easily produce sufficient amounts of quality fodder for dairy cows and feed for poultry from WRF-7 dual-purpose triticale during periods of severe fodder shortages. DOI: http://dx.doi.org/10.3329/pa.v19i2.16964 Progress. Agric. 19(2): 217 - 228, 2008